Multiple Grammatical Parsing (I‘rāb) in Qur’anic Syntax and Its Rhetorical Impact – A Descriptive Approach - zehar, mohammedr (El Omda in Linguistics and Discourse Analysis, 2023)
Ancient, modern, and even contemporary linguists unanimously agreed that the Qur’anic discourse and the Qur’anic sentence in particular have a distinct pattern and structure that underlie many mysteries, and in which various forms and images of miraculousness are determined, through their inherent practice of the texts of the Arabic language. The Qur’anic sentence has semantic characteristics that are unique to it, and technical characteristics that qualify it for the rest of the linguistic structures that humans accomplish. This article reveals the places of miracles in the multiplicity of syntactic aspects in the Qur’anic texts, which is based on syntactic similarity, and the accuracy of meanings, while recording the students’ position on the grammatical and rhetorical heritage of it